Village fund Village Fund Usage Improvement Strategy in the Effort to Reduce Poverty in Bogor District - Teguh Imanto; Dwi Rachmina; A. Faroby Falatehan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The primary objective of the Village Fund (Dana Desa) is to enhance village autonomy through community development and empowerment, aiming to alleviate poverty. Nationally, the allocation of the Village Fund reached IDR 538.94 trillion during 2015–2023. However, this increase has not had a significant impact on poverty reduction in Bogor Regency. Expenditures relevant to poverty alleviation, as stipulated in Minister of Home Affairs Regulation No. 20 of 2018, primarily fall under the community empowerment sector, as they directly relate to human capital development and village infrastructure. This research aims to (1) analyze the utilization of the Village Fund in poverty reduction efforts in Bogor Regency and (2) formulate strategies for its improvement. The data utilized includes primary data from 20 respondents and secondary data from the BPKP SISKEUDES system, encompassing all planning and realization data for the Village Fund across 416 villages during the 2019–2023 period. Analytical methods employed include simple regression, descriptive analysis, SWOT analysis, and QSPM (Quantitative Strategic Planning Matrix). The research findings indicate that expenditures in the community empowerment sector have not significantly impacted poverty reduction. This is attributed to their persistently low proportion (12.09%) and the suboptimal management of Village-Owned Enterprises (BUM Desa), which contribute, on average, only 10.50% to the village's original revenue (PAD). Furthermore, a significant majority of villages (approximately 71%) that provided capital to BUM Desa have yet to generate any PAD. Therefore, strategies to enhance Village Fund utilization include synergistic oversight through joint audits, optimizing human resources and technology, and strengthening information systems in Village Fund management to support effective village development.